Hematocrit Changes as Parameters for Giving Mannitol in Severe Head Injury - Donny Valensius Susanto; Trijoso Permono (Sriwijaya Journal of Surgery, 2018)
ABSTRACT Introduction. Incidence of head injuries is also quite high in Indonesia, around 1.4 million cases per year with a mortality rate of 15-20% in the population aged 5 to 35 years. Head injuries are commonly divided into two separate time periods namely primary and secondary brain injuries. Primary brain injury is physical damage to the parenchyma (tissue and blood vessels) that occurs during a traumatic event, thus causing compression of the surrounding brain tissue. Secondary brain injury is a continuation of the results of primary brain injury with the main complications of brain injury in the following hours and days. This study was aimed to asses the benefits of administration of mannitol in cases of severe head injury in South Sumatra, Indonesia. Methods. This research was a clinical trial without comparison by looking at hematocrit levels in patients with severe head injuries with intracranial hypertension before and after given mannitol therapy. Data analysis was performed with IBM SPSS Version 23. Data was presented in the form of narrative tables. Then the paired T test was performed. P value <0.05. Results. From 39 research subjects, the age of the subjects ranged between 6-88 years with an average of 33 years. Based on sex there were 28 male sufferers (71.8%) and there were 11 female sufferers 28.2%. GCS varies from 3 to GCS 8 intra-cranial abnormalities. From 39 research subjects with severe head injury without surgery, a hematocrit examination was performed before, after 10 minutes and 6 hours of injection of mannitol bolus 1 g / kg body weight. It was obtained that averaged hematocrit before mannitol administration was 34, after 10 minutes was 33 and after 6 hours was 35. Conclusion. There is a decrease in hematocrit levels after administration of bolus mannitol 1 g / kg BW at the beginning of mannitol administration and hematocrit will increase again after 6 hours of mannitol administration